How to De-Ruse sociobiological theory of knowledge - Życiński, Joseph (Theoria et Historia Scientiarum, 2007)
In this paper I try to answer what precisely is meant by the mysterious „attraction”, and how can a critical version of sociobiological epistemology be reconciled with the standpoint of metascientific rationalism. My answer to the latter question is that sociobiology and rationalism can be reconciled only if one rejects, or substantially modifies, those statements in Ruse’s expositions that seem much closer to rhetoric than to critical metascientific reflection.